Indirect ELISA (iELISA) for routine detection of antibodies against Minute Virus of Mice (MVM) in mice colonies - Laborde, Juan Martin (2017)
In this study we developed an indirect ELISA to detect antibodies against Minute Virus of Mice (MVM) using an antigen produced from BHK-21 cells infected with a prototype strain of the virus. The optimal antigen concentration and serum dilutions were established. In order to analyze variability in the laboratory, reproducibility and repeatability within and between plates were determined. Then, a panel of 460 sera from conventional facilities and previously classified as positive or negative by the indirect fluorescent antibody assay was analyzed. The cutoff value was determined by a receiver operating characteristic (ROC) curve. The results of the indirect ELISA were compared with those of the indirect fluorescent antibody assay. The ELISA assay showed 100% sensitivity and 99% specificity. ELISA is a useful tool to be developed in standard virology laboratories and can be used for screening animals faster than the traditional indirect fluorescent antibody assay.